Numerical Experimentation on Argentina Nano Focus Machine - Arwinder, Singh; Teh, Thiam Oun; Saw, Sor Heoh; Lee, Sing (Akademi Sains Malaysia, 2021)
Introduction: Argentina Nano Focus Machine is a small transportable dense plasma focus used as a portable intense, fast neutron source. Methods: The objective of this paper is to show that by using only one experimental current waveform together with the actual machine and operating parameters, the Argentina Nano Focus Machine could be numerically modelled to enable the study of its plasma dynamics and its yield of ion beams and fusion neutrons. Results: The computed results agree reasonably with the measured in terms of the peak current (computed of 55 kA compared to the measured value of 62 kA), the radial phase start time and the duration of the pinch phase (computed 49 ns compared to experimentally estimated of 50 ns). Conclusion: This demonstrates that the code is a valuable tool to complement the actual experiment by correctly computing the axial and radial trajectories' dynamics through the measured current waveform. Additionally, the code also produces the variation of ion beam energy and neutron yield as functions of pressure, for which there is no published experimental data.